Recombinant viruses as vaccines against viral diseases. - Souza, A; Haut, L; Reyes-Sandoval, A; Pinto, A (2005)
Vaccine approaches to infectious diseases are widely applied and appreciated. Amongst them, vectors based on recombinant viruses have shown great promise and play an important role in the development of new vaccines. Many viruses have been investigated for their ability to express proteins from foreign pathogens and induce specific immunological responses against these antigens in vivo. Generally, gene-based vaccines can stimulate potent humoral and cellular immune responses and viral vectors might be an effective strategy for both the delivery of antigen-encoding genes and the facilitation and enhancement of antigen presentation. In order to be utilized as a vaccine carrier, the ideal viral vector should be safe and enable efficient presentation of required pathogen-specific antigens to the immune system. It should also exhibit low intrinsic immunogenicity to allow for its re-administration in order to boost relevant specific immune responses. Furthermore, the vector system must meet criteria that enable its production on a large-scale basis. Several viral vaccine vectors have thus emerged to date, all of them having relative advantages and limits depending on the proposed application, and thus far none of them have proven to be ideal vaccine carriers. In this review we describe the potential, as well as some of the foreseeable obstacles associated with viral vaccine vectors and their use in preventive medicine.